Efficacy and safety of switching from ticagrelor to clopidogrel during the early and late phase in acute coronary syndrome patients after percutaneous coronary intervention. (2nd April 2020) - Wang, Chenggang; Zheng, Wen; Shaqdan, Ayman; Wang, Chunmei; Qin, Xiuchuan; Zhao, Xuedong; Wang, Xu; Yuan, Lin; Nie, Shaoping; Liu, Ran
Abstract: In patients with acute coronary syndrome (ACS), treatment using ticagrelor demonstrated significant ischemic benefits over clopidogrel; however, it was associated with increased bleeding complications leading to frequent de-escalation to clopidogrel. The objective of the present study was to investigate the efficacy and safety of de-escalation in early and late phase after percutaneous coronary intervention (PCI). We performed a retrospective study of 4678 ACS patients from March 2016 to April 2017 who initially received ticagrelor then de-escalated to clopidogrel and categorized them into Group 1: early phase (1–30 days) and Group 2: late phase (>30 days–1 year) switching groups. The primary efficacy endpoints included cardiovascular death, definite/probable stent thrombosis, myocardial infarction, unplanned revascularization, and stroke. The safety endpoint was Bleeding Academic Research Consortium classification 3 or 5 bleeding events within 1 year after PCI. The incidence of switching occurred in 1019 patients; 380 (37.3%) in Group 1 (median 14 days, interquartile range 4–30 days) versus 639 (62.7%) in Group 2 (median 180 days, interquartile range 90–270 days). The ischemic endpoints occurred in 53 (13.9%) patients in Group 1 versus 35 (5.4%) in Group 2 (HR 1.93, 95%CI 1.22–3.08, p < .0001). There were no significant differences of major bleeding events (HR 0.91; 95%CI, 0.58–1.43, p = .90) seen between the groups. The main cause for switching between the two groups was due to BARC 1 or 2 bleeding types. Early de-escalation from ticagrelor to clopidogrel during the initial 30 days after ACS was associated with higher risk of ischemic events when compared with switching beyond 30 days.